Financial Controlling Tasks in Financing Companies of Various Sizes - Tobias BUETTNER (Communications of International Proceedings, 2024)
In today's business world, local businesses are under constant pressure to reduce costs and streamline operations. As the Chairman of the Board of a medium-sized German company, I experience on a daily basis how important financial controlling has become in the financing of companies of different sizes. In the first part, I will discuss financial control as a part of the company and list its tasks. In the second part of this short paper, I will present the tools that can be used in financial controlling, followed by the different practices in small, medium and large companies, supported by short practical examples.
Keywords: Finance; controlling; management; companies; SMEs; investment and financing ratios; financial reporting and value reporting; cash flow statement and financial analysis